INTEGRATING PROJECT-BASED LEARNING WITH SOCIO-SCIENTIFIC ISSUES IN SCIENCE EDUCATION: A SYSTEMATIC LITERATURE REVIEW - Ningsih, Widia; Suwanto, Fevi Rahmawati; Fairuz, Tariza (Universitas Tanjungpura, 2026)
This systematic literature review examines the integration of Project-Based Learning (PjBL) with Socio-Scientific Issues (SSI) in science education, focusing on mapping empirical findings, implementation patterns, and research gaps that have not been widely studied. This study aims to identify the learning outcome variables measured, describe the characteristics of PjBL–SSI implementation, and reveal the main challenges and limitations of previous studies. Using PRISMA guidelines, 6 peer-reviewed journal articles (n = 6) published between 2020 and 2025 were analyzed. These articles covered various educational levels, from elementary school to higher education, with diverse research designs. The results of the study show that the integration of PjBL with SSI consistently has a positive impact on students' critical thinking, problem-solving, science literacy, digital literacy, and ethical awareness, especially through involvement in real-issue-based projects that require multidimensional analysis and value-based decision-making. However, this study also identified a number of key challenges, namely the limited readiness of teachers in designing SSI-based projects, the lack of standardized learning resources and assessment tools, and the dominance of research focus on the cognitive domain. Another important finding shows that the affective, social, and reflective aspects of students have received relatively little attention in previous studies, thus opening up opportunities for further research. Overall, this review provides a conceptual contribution by presenting a structured synthesis of the characteristics, impacts, and challenges of PjBL–SSI integration, as well as a practical contribution as a reference for educators and curriculum developers in designing contextual, relevant, and socially responsible science learning.